Laboratory assessment of vibration emissions from vibrating forks used in simulated beach cleaning - McDowell, T.W.; Xu, X.S.; Warren, C.; Welcome, D.E.; Dong, R.G. (Canadian Acoustics, 2011)
The vibrations associated with the use of vibrating manure forks are characterized and the vibration exposure time limits based on the recommendations of ANSI S2.70-2006 are estimated. To investigate the vibration exposures associated with these operations, a laboratory study was performed on the vibrations produced by the forks operated during simulated beach cleaning. The test apparatus for the laboratory study consisted of a mortar-mixing tub filled with a homogenous mixture of moist sand and debris. Vibration data were collected for eight seconds per trial. ANOVA results indicate that the mean acceleration for the fast fork was significantly higher than that for the slow fork. The slow fork with the mesh basket could be operated at full throttle for almost three hours before reaching the action value.